MENINGKATKAN KEUNGGULAN KOMPETITIF PERUSAHAAN PERENCANA DI PASAR GLOBAL: Sebuah Kajian Literature - Roza, Fielda; Peli, Martalius; Khadavi, Khadavi; Ariani, Vivi (Fakultas Teknik, Universitas Riau Kepulauan, 2024)
Rapid change in global marketplace offers formidable challenges to firms in the construction industry. Firms need to understand the nature of internal and external environment and apply competitive strategy that suits the firms‟ objectives to keep an edge over competition. Offering professional service in the industry, Construction firms are different than product-based industry in terms services provided, relationship between firm-client and competing style with the existing and new firms. How do Construction firms compete and what strategies are suitable for them? There are four competitive strategies such as cost leadership, focus, differentiation and growth to enhance the ways of competing style. How does the competitive strategy chosen impact the business performance? A success of any strategy adopted is determined by the performance of the firm. Thus, this paper stressed that for a Construction firm to maintain their competitive advantage, they need to relate the company performance with the competitive strategy adopted.